A Correlational Study of Serum Alkaline Phosphatase Level and Developmental Mandibular Laterognathism. Issue 2 (March 2015) - Dai, Jiewen; Li, Hongliang; Yu, Hongbo; Si, Jiawen; Fang, Bing; Shen, Steve Guofang
<x xml:space="preserve">Abstract</x> Abstract The abnormal cartilage/bone metabolism in unilateral condyle may be a direct factor that contributes to developmental mandibular laterognathism. However, although many molecules have been demonstrated to play crucial roles in the development of temporomandibular joints, the exact molecular mechanisms that lead to the disrupted condylar cartilage/bone development were greatly unknown. In this retrospective study, our findings revealed that serum alkaline phosphatase (ALP) level in adult patients with developmental mandibular laterognathism was lower than that in control subjects, and the serum ALP levels continue to reduce in adult patients (>20 years old). Although the exact relationship between the lower serum ALP level and developmental mandibular laterognathism is unclear, the findings further support the opinion that the condylar growth may sustain for a long time in the affected condyle in patients with developmental mandibular laterognathism and offer an alternative choice to use total serum ALP activity as a possible biomarker to assess condylar growth activity in patients with developmental mandibular laterognathism.